Penerapan Zahir Accounting Untuk Menyusun Laporan Keuangan Pada Sekolah Ra Az-Zahra - Siti Fatimah; Sifa Fauziah; Yudhistira Yudhistira (LPPM Universitas Bina Sarana Informatika, 2021)
Along with the development of increasingly rapid and sophisticated information technology in the current era of globalization, it has provided many benefits in doing a job. One of them is in the field of education, which can help school activities run effectively and efficiently in making financial reports to facilitate the process of analyzing financial statements. So that school leaders can see more clearly the financial condition based on accurate data. However, currently, RA Az-Zahra's school in making reports still uses written accounting records, from recording transactions to making financial reports such as tuition income, exam income, other income obtained from uniform sales, cash out and operational costs. Sometimes this causes errors in the accounting cycle process due to irregular recording and storage of transaction data, and is less effective than using a computerized system. The results of recording financial statements using Zahir Accounting show results that are balanced with the results of recording manual financial statements. So to overcome this problem, the application of Zahir Accounting is a solution to reduce the risk of errors in the accounting cycle recording process so that it can produce financial reports more quickly, accurately and efficiently. that can be used for interested parties as users of financial statements.